Анализа корелације цитокина Тх1/Тх2 и показатеља јетрене фиброзе код пацијената са хроничним хепатитисом Б: Цитокини Тх1/Тх2 и показатељи јетрене фиброзе код хроничног хепатитиса Б - Yu, Chun; Chen, Meiling; Han, Xiaonan; Feng, Yu-Hang; Sun, Hongwei; Yang, Hong (Journal of Medical Biochemistry, 2025)
Objective: To investigate the potential therapeutic benefits of autoimmune antibody detection in individuals suffering from chronic hepatitis B. Methods: For the observation group, 102 patients with chronic hepatitis B who were admitted between March 2022 and March 2025 were chosen. Additionally, the control group consisted of 102 healthy people who were examined throughout the same time period. The two groups' autoimmune antibodies were identified, and patients in the observation group with positive and negative autoimmune antibodies were compared in terms of their liver function, liver fibrosis markers, and cytokine levels. Results: The total positive rate of autoimmune antibodies in the observation group was 26.47%, whereas it was 3.92% in the control group (P
Keywords: Hronični hepatitis B; Аутоимуни антитела; Фиброза јетре; Цитокини Тх1/Тх2